A Conserved Di‐Basic Motif of Drosophila Crumbs Contributes to Efficient ER Export. (14th April 2015) - Kumichel, Alexandra; Kapp, Katja; Knust, Elisabeth
<x xml:space="preserve">Abstract</x> The Drosophila type I transmembrane protein Crumbs is an apical determinant required for the maintenance of apico‐basal epithelial cell polarity. The level of Crumbs at the plasma membrane is crucial, but how it is regulated is poorly understood. In a genetic screen for regulators of Crumbs protein trafficking we identified Sar1, the core component of the coat protein complex II transport vesicles. sar1 mutant embryos show a reduced plasma membrane localization of Crumbs, a defect similar to that observed in haunted and ghost mutant embryos, which lack Sec23 and Sec24CD, respectively. By pulse‐chase assays in Drosophila Schneider cells and analysis of protein transport kinetics based on Endoglycosidase H resistance we identified an RNKR motif in Crumbs, which contributes to efficient ER export. The motif identified fits the highly conserved di‐basic RxKR motif and mediates interaction with Sar1. The RNKR motif is also required for plasma membrane delivery of transgene‐encoded Crumbs in epithelial cells of Drosophila embryos. Our data are the first to show that a di‐basic motif acts as a signal for ER exit of a type I plasma membrane protein in a metazoan organism. <inline-graphic xlink:href="ark:/27927/pgjn19dxsk" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />